Cover Picture: Black phosphorus: Versatile two‐dimensional materials in cancer therapies (View 1/2021). Issue 1 (6th February 2021) - Ding, Jie; Qu, Guangbo; Chu, Paul K.; Yu, Xue‐Feng
Abstract : As a fledgling class of 2‐dimensional materials with excellent and unique properties, black phosphorus nanosheets (BPs) have promising prospects in biomedical applications. In article number 20200043, Xue‐Feng Yu, Guangbo Qu and their colleagues summarize and discuss recent progress related to the application of BPs to different tumor therapies such as phototherapy, radiotherapy, bioactive phospho‐therapy and diagnosis‐combined therapy.